Laughter and Well-Being: The Transformative Experiences of Working Mothers - Jhonna G. Toledo; Araceli C. Doromal (Philippine Social Science Journal, 2024)
This study explores how laughter therapy transforms the experiences of working mothers, impacting their stress, resilience, and well-being. Six participants engaged in unstructured interviews, analyzed through a descriptive phenomenological approach. Findings revealed that both genuine and simulated laughter offer therapeutic benefits, improving optimism, stress management, and sleep. Laughter's contagious nature strengthens social bonds and promotes shared joy. The therapy fosters emotional resilience, enhances health, and nurtures spirituality, contributing to inner peace. Accessible and holistic, laughter therapy empowers working mothers to face challenges with resilience and optimism, ultimately improving their quality of life.